Visual Business Planning: Effects of BMC-Centered Training on Entrepreneurial Mindset and Sales among MSME Owners in Yogyakarta - Mart Sasongko, Rolan; Sunaryo Nainggolan, Dedy; Rifky Adiyatna, Hafidh; Alvin Mubarok, Alvian; Purnomo Saputro, Budi; Ryan Setya Budi (Dinasti Review, 2025)
Micro, small, and medium enterprises (MSMEs) are central to Indonesia’s economy yet often lack practical capabilities in business planning, promotion, and post-pandemic adaptation. This study evaluates a municipal–university program in Yogyakarta (2023) that delivered eight in-person sessions (32 hours) centered on the Business Model Canvas (BMC), complemented by modules on promotion, finance, and operations, and followed by incubator pairing and community mentors. MSME owners (n = 452) completed a post-training survey, and training exposure was indexed from attendance/engagement and canvas completion (0–100). Entrepreneurial mindset was measured with five Likert items; self-reported sales growth served as a secondary outcome. Using simple linear regression with full assumption checks and robustness tests, greater BMC training exposure was positively associated with entrepreneurial mindset, and higher exposure corresponded with encouraging directional signals for sales growth. Model diagnostics indicated adequate fit and stability to alternative exposure weightings and exclusion of influential observations. Overall, a month-long, mentor-supported program that centers on visual business planning appears feasible for scaling MSME capability building and is associated with stronger entrepreneurial mindset among participants. Future evaluations should incorporate pre–post or comparison designs and objective performance indicators to validate and extend these findings.